PUBLIC INTEREST IN GOLD INVESTMENTS BASED ON PROFIT AND ASSET VALUE: MINAT MASYARAKAT TERHADAP INVESTASI EMAS BERDASARKAN KEUNTUNGAN DAN NILAI ASET - Mahfud Asrof; Adinda Putry Lestari; Ahmad Quraisy Syihab (Universitas Wahid Hasyim Semarang, 2026)
Gold investment is a popular investment option because it offers potential returns while preserving asset value over the long term. This study examines the influence of profit aspects and asset value on public interest in gold investment among customers of Gerai Dinar Pekalongan. A quantitative approach with an associative design was employed. The population consisted of 252 customers, and 100 respondents were selected using purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using SPSS version 24 with validity, reliability, classical assumption, multiple linear regression, t-test, F-test, and coefficient of determination (R²) The results show that the profit aspect has a positive and significant effect on public interest in gold investment, with a regression coefficient of 0.493 (t = 6.944; p = 0.000). Asset value also has a positive and significant effect, with a regression coefficient of 0.497 (t = 6.814; p = 0.000). Simultaneously, both variables significantly influence investment interest (F = 372.995; p = 0.000). The adjusted R² value of 0.883 indicates that the model explains 88.3% of the variation in public interest. The study concludes that profit aspects and asset value are the main determinants of public interest in gold investment.